Development of a Character-Based Human Resource Management Model from an Educational Administration Perspective - Firmansyah, Firmansyah; Irfan, Muhammad; Sartika, Renni; Haeril, Haeril; Hidayatullah, Arief (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research aimed to explore and identify the challenges and potentials associated with the development of a human resource management (HRM) model oriented towards character education at Mbojo Bima University, West Nusa Tenggara. This research utilized a qualitative descriptive method involving observation, interviews, and documentation at the campus level of Mbojo Bima University. The findings and discussions of this research highlighted the importance of selecting teaching staff and employees who are committed to character education, developing education programs that encompass character and moral values, integrating character values into the curriculum, developing policies and procedures that support the formation of student character, as well as evaluating and improving the quality and relevance of character education programs. It is expected that the findings of this research will contribute significantly to improving the quality of higher education in Indonesia and strengthen the character and morality of the younger generation.